Global spillover of land-derived microbes to Ocean hosts: Sources, transmission pathways, and one health threats - Hai-Chao Song; Hany Elsheikha; Tao Yang; Wei Cong (Environmental Science and Ecotechnology, 2025)
Terrestrial pathogens are increasingly being detected in marine organisms, raising concerns about ecosystem sustainability, biodiversity loss, and threats to human health. Over the past two decades, reports of microbial contaminants crossing from land to sea have increased, suggesting shifts in pathogen ecology driven by environmental changes and human activities. Pathogens originating on land can spread, adapt, and persist in marine environments, infecting a wide range of hosts and potentially re-entering terrestrial environments. Despite growing recognition of this issue, a comprehensive understanding of the distribution, diversity, and transmission pathways of these pathogens in marine ecosystems remains limited. In this Review, we provide a global analysis of terrestrial pathogen contamination in marine animal populations. Drawing from pathogen detection data across 66 countries, we used phylogenetic methods to infer land-to-sea transmission routes. We identified 179 terrestrial pathogen species, including 38 bacterial, 39 viral, 80 parasitic, and 22 fungal species, in 20 marine host species. Terrestrial pathogens are not only widespread but also highly diverse in marine ecosystems, highlighting the frequency and ecological significance of cross-system microbial exchange. By revealing the scale and complexity of land-to-sea pathogen flow, we show that climate change, pollution, and other anthropogenic pressures may intensify pathogen spillover events, with potential feedback effects on terrestrial systems. This highlights the urgent need for integrated surveillance and policy frameworks acknowledging the interconnectedness of terrestrial and marine health. Our work advocates a One Health approach to microbial ecology, stressing the need to safeguard marine and human populations from emerging cross-system threats.